Peyer's patch-specific lymphocyte homing receptors consist of a VLA-4-like alpha chain associated with either of two integrin beta chains, one of which is novel. - Holzmann, B (1989)
Lymphocytes home to various lymphoid organs by adhering to and migrating through specialized high endothelial venules (HEV). The murine cell surface heterodimer LPAM-1 is involved in the homing of lymphocytes to mucosal sites (Peyer's patches). LPAM-1 has an alpha subunit (alpha 4m) analogous to the alpha chain of the human integrin molecule VLA-4. Here we show that the LPAM-1 beta subunit (beta p) is immunochemically and biochemically distinct from previously defined integrin beta subunits, suggesting that beta p represents a novel integrin beta subunit. Depending on the cellular source two alternative beta subunits, beta p and integrin beta 1, can be isolated in association with alpha 4m. Therefore, alpha 4m is the common subunit of the unique integrin LPAM-1 (alpha 4m beta p) and of the heterodimer LPAM-2 (alpha 4m beta 1), which is analogous to VLA-4. Antibody-blocking experiments suggest that, in addition to LPAM-1, LPAM-2 is also involved in the organ-specific adhesion of lymphocytes to Peyer's patch HEV.